THE TURKISH-RUSSIAN RELATIONS IN THE ERA OF AKP - Mohamad ARAFAT; Mahmood Alnuaimy (Afyon Kocatepe Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi, 2015)
This research deals with the bilateral relations between Turkey and Russian Federation in the political, diplomatic and economic fields, during the years (2000-2009), where it witnessed a big development during this period which is considered the best in the history of the relations between the two states, due to the change of the political systems in the two countries, and its pursuing a balanced and effective foreign policy in their regional environment, that contributed in promoting and enhancing its bilateral relations, and deepen their cooperation horizons in the different fields and areas, besides of arrangement their attitudes toward a number of common essential issues.